Bats roost site preferences in wind cave nature reserve, Bau, Sarawak - Muhd Amsyari, Morni; Faisal Ali, Anwarali Khan; Qhairil Shyamri, Rosli; Julius Willian, Dee; Roberta Chaya, Tawie Tingga; Muhd Ridwan, Abd Rahman (Malaysian Society of Applied Biology, 2018)
Roosting site plays a vital role in bats existence as it provides protection from predators and bad weather. Unfortunately, little is known about bats roost preferences in Malaysia. Therefore, this study was conducted to determine roosting preferences of cave dwelling bats in Wind Cave Nature Reserve (Wind Cave NR). Cave microclimate and physiological parameters that were analysed in this study include roost temperature, humidity, distance of the roosting site from the nearest cave entrance and the sound intensity at bat’s roosting site. HOBO data logger was used for taking temperature and humidity level. Leica Disto D3 range finder was used to measure roost distance whereas sound intensity was recorded using Decibel Meter Version 1.6 application. There were ten species of bats from five families found roosting in Wind Cave NR. The Canonical Corresponding Analysis showed four groupings with p-value<0.0001. We also presented the relationship between bats natural diet with its ability to cope with fluctuations in roost’s microclimate. Cave physical parameters appeared to influence bats roost selection in respect to its body size and echolocation ability. Knowing these parameters helps in better understanding of roosting preferences that is important for conservation of cave bats in Malaysia.